An adaptive harmonic compensation strategy for three-phase shunt active power filter based on double second-order generalized integrator with prefilter - Kalkoul, Sami; Benalla, Hocine; Nabti, Khalil; Abdellatif, Reama (Національний технічний університет "Харківський політехнічний інститут", 2020)
This study presents a straightforward adaptive prefiltering algorithm based on a double second-order generalized integrator with prefilter to solve one of the power quality issues, this algorithm is in charge of the determination of the reference harmonic currents in the control of three-phase shunt active power filter which presents an effective way to enhance the grid current quality. The proposed algorithm is used twice, to extract the harmonic currents produced by the non-linear loads and be an interesting part in the estimation of the frequency and amplitude of the fundamental voltage in various anomalies which can be noticed on the grid voltage. The performance, precision, and robustness of the proposed method are evidenced under balanced, unbalanced, and distorted grid voltage in the simulation and experimental results obtained by the implementation of the shunt active power filter on MATLAB-Simulink environment and the dSPACE 1104 platform respectively.

В данной работе представлен простой адаптивный алгоритм предфильтрации, основанный на двойном обобщенном интеграторе с предфильтром второго порядка (DSOGI-WPF) для решения одного из вопросов качества электроэнергии. Данный алгоритм отвечает за определение опорных гармонических токов при контроле трехфазного фильтра шунта активной мощности (SAPF). Предложенный алгоритм используется дважды: для извлечения гармонических токов, создаваемых нелинейными нагрузками, и также является интересной частью оценки частоты и амплитуды основного напряжения при различных аномалиях, которые можно заметить по напряжению сети. Эффективность, точность и надежность предложенного метода подтверждаются при сбалансированном, несбалансированном и искаженном напряжении сети результатами моделирования и экспериментов, полученными при реализации SAPF в среде MATLAB-Simulink и платформе dSPACE 1104, соответственно.
Keywords: SOGI-WPF; SAPF; power quality; DSOGI-PLL-WPF; обобщенный интегратор с предфильтром второго порядка (SOGI-WPF); фильтр шунта активной мощности (SAPF); качество электроэнергии; двойной обобщенный интегратор с предфильтром второго порядка с фазовой синхронизацией (DSOGI-PLL-WPF)